1998
DOI: 10.1111/j.1440-1673.1998.tb00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Failed magnetic resonance imaging examinations due to claustrophobia

Abstract: A recognized cause of incomplete or cancelled MRI examinations is anxiety and claustrophobic symptoms in patients undergoing MR scanning. This appears to be a problem in many MRI centres in Western Europe and North America, where it is said to be costly in terms of loss of valuable scan time, and has led to researchers suggesting several anxiety-reducing approaches for MRI. To determine the incidence of failed MRI examination among our patients and if there are any associations with a patient's sex, age and ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 9 publications
2
33
0
3
Order By: Relevance
“…In the study most patients declared that they had not received any information from the health personnel prior the examination and also as indicated in Table 3, most of the patients who had no prior information were anxious, this showed that when little or no information are given to the patients it creates worry hence increasing anxiety [7].The other patients who affirmed to have had receive knowledge and were still anxious maybe due their inability to absorb information given to them by their caregivers confirming the research carried out by Sarji et al, [8].…”
Section: Pre-procedural Anxiety Levelssupporting
confidence: 71%
“…In the study most patients declared that they had not received any information from the health personnel prior the examination and also as indicated in Table 3, most of the patients who had no prior information were anxious, this showed that when little or no information are given to the patients it creates worry hence increasing anxiety [7].The other patients who affirmed to have had receive knowledge and were still anxious maybe due their inability to absorb information given to them by their caregivers confirming the research carried out by Sarji et al, [8].…”
Section: Pre-procedural Anxiety Levelssupporting
confidence: 71%
“…Higher rates of claustrophobia have been reported among middleaged women compared with the rates reported among other demographic groups ( 14 ), and a correlation with higher education levels and higher socioeconomic status has been reported ( 15 ). Although hypnosis ( 16 ) and anxiolytic agents such as lorazepam or diazepam can be used effectively to reduce claustrophobia, they may not be generally accepted for screening.…”
Section: Breast Imaging: Elevated Breast Cancer Risk and Refusal For mentioning
confidence: 94%
“…Claustrophobia has been well recognized in MRI. It has been reported that up to 35% of patients undergoing MRI experience claustrophobia (Sarji, Abdullah, Kumar, Tan, & Narayanan, 1998) preventing imaging in 0.88% to 4.3% of cases (Danterndorfer, Wimberger, Katschnig, & Imhoff, 1991;Flaherty & Hoskinson, 1989). In PET, the length of the study, the size of the imaging bore, and patient positioning are comparable to that of MRI; hence, encountering claustrophobia in patients undergoing PET imaging is to be expected with similar prevalence.…”
Section: Before Arrivalmentioning
confidence: 96%